2003
DOI: 10.1590/s0100-29452003000300042
|View full text |Cite
|
Sign up to set email alerts
|

Produção e partição de matéria seca e abertura estomática do limoeiro 'Cravo' submetido a estresse salino

Abstract: O presente trabalho teve como objetivo avaliar a influência da salinidade sobre alguns parâmetros fisiológicos do limoeiro 'Cravo' (Citrus limonia Osbeck), principal porta-enxerto da citricultura baiana. Esses estudos são importantes, porque podem viabilizar a utilização de água de baixa qualidade para irrigação, com vistas a melhoria da produtividade dessa cultura. Sementes de limão 'Cravo' foram selecionadas quanto ao tamanho e colocadas para germinar em areia lavada. Três dias após a germinação as plantas f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
23

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 7 publications
0
4
0
23
Order By: Relevance
“…This showed that even receiving a higher light intensity, the sun leaves had important morphoanatomic adaptations, allowing the same stomatal conductance and CO 2 intercellular concentration of the shade plants, also in agreement with the unchanged photosynthetic rate between the two types of leaves In Mangifera indica, Castro Neto (2003) observed a lower stomatal conductance in sun leaves in the beginning of the irrigation period (end of May to August), suggesting this to occur due to the end of the water deficit period, since under irrigation, stomatal conductance increase although remaining lower than in the water deficit period. Cruz et al (2003) observed in the cravo lemmon tree submitted to saline stress, a lower stomatal conductance, with increased salinity content. Sultana et al (1999) emphasized that a lower leaf stomatal conductance obtained by the plants under saline stress was probably related to the water stress to which these plants were subjected, as the leaves exposed to higher light.…”
Section: Figure 3 -Transpiration Rate Of Lithraea Molleoides Leaves Dmentioning
confidence: 73%
“…This showed that even receiving a higher light intensity, the sun leaves had important morphoanatomic adaptations, allowing the same stomatal conductance and CO 2 intercellular concentration of the shade plants, also in agreement with the unchanged photosynthetic rate between the two types of leaves In Mangifera indica, Castro Neto (2003) observed a lower stomatal conductance in sun leaves in the beginning of the irrigation period (end of May to August), suggesting this to occur due to the end of the water deficit period, since under irrigation, stomatal conductance increase although remaining lower than in the water deficit period. Cruz et al (2003) observed in the cravo lemmon tree submitted to saline stress, a lower stomatal conductance, with increased salinity content. Sultana et al (1999) emphasized that a lower leaf stomatal conductance obtained by the plants under saline stress was probably related to the water stress to which these plants were subjected, as the leaves exposed to higher light.…”
Section: Figure 3 -Transpiration Rate Of Lithraea Molleoides Leaves Dmentioning
confidence: 73%
“…Stomatal closure is one of the first defense mechanism of the plants under stress, reducing leaf transpiration, besides causing reduction in the normal CO 2 flow towards the carboxylation site, and gs is one of the main responsible for the reduction of photosynthesis in plants cultivated under saline conditions (Cruz et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Segundo Macêdo et al (2005), que também obtiveram resultados semelhantes com bananeira, em alta salinidade, a expansão celular pode ser reduzida pelo acúmulo de sais na parede celular, reduzindo o turgor e, consequentemente, o crescimento. De acordo com Cruz et al (2003), o acúmulo de íons Na + dá-se preferencialmente nas folhas mais velhas, provavelmente por ser um mecanismo adaptativo para proteger os ápices e as folhas fisiologicamente mais ativas. A diminuição da produção de folhas vivas pode estar relacionada não só ao efeito do sal, mas também à ausência dos fitorreguladores; tal redução pode ser devido à incapacidade de a planta produzir novas folhas mais rapidamente que a senescência (MUSCOLO et al, 2003), além da morte das folhas mais velhas por necrose de seus tecidos.…”
Section: Resultsunclassified